Immediate tumor resection in patients with locally advanced gastroesophageal adenocarcinoma with nonresponse to chemotherapy after 4 weeks of treatment versus resection after completion of chemotherapy (OPTITREAT trial, DRKS00004668): study protocol for a randomized controlled pilot trial. Issue 1 (December 2016) - Blank, Susanne; Knebel, Phillip; Haag, Georg-Martin; Bruckner, Thomas; Klaiber, Ulla; Burian, Maria; Schaible, Anja; Sisic, Leila; Schmidt, Thomas; Diener, Markus; Ott, Katja
Abstract Background Neoadjuvant chemotherapy is a standard of care for patients with adenocarcinoma of the esophagus and stomach in Europe, but still only 20–40 % respond to therapy and the critical issue; how to treat nonresponding patients is still unclear. So far, there is no randomized trial evaluating the impact of early termination of neoadjuvant chemotherapy and immediate tumor resection in nonresponding patients with locally advanced gastroesophageal cancer on postoperative outcome. With this exploratory pilot trial, we want to get first estimates about the effect of discontinuation of chemotherapy with the aim to plan and conduct a further definitive trial. Methods/design OPTITREAT is designed as a single-center, randomized controlled pilot trial with two parallel study groups. Four weeks after starting neoadjuvant chemotherapy in all patients, clinical response will be assessed by endoscopy and endosonographic ultrasound. Then, nonresponding patients (n = 84) will be randomized in a 1:1 ratio to intervention group with stopping chemotherapy and immediate tumor resection or control group with completion of chemotherapy before surgery. Outcome measures are overall survival, R0 resection rate, perioperative morbidity and mortality, histopathological response, and quality of life. Statistical analysis will be based on the intention-to-treat population. Due to the study design as an explorative pilot trial, no formal sample size calculation was performed. The planned total sample size of 120 patients is considered ethical and large enough to show the feasibility and safety of the concept. First data on differences between the study groups in the defined endpoints will also be generated. Discussion Individualized therapy is of utmost interest in the treatment of locally advanced gastroesophageal adenocarcinoma as less than half of the patients show objective response to current chemotherapy regimens. The findings of the OPTITREAT trial will help to get first data about clinical response evaluation followed by immediate tumor resection in nonresponding patients after 4 weeks of neoadjuvant chemotherapy. Based on the results of this pilot study, a future confirmatory trial will be planned to prove efficacy and evaluate significance. Trial registration German Clinical Trial Register number:DRKS00004668